2008
DOI: 10.1007/s00709-008-0291-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the plasma membrane during exposure to low temperatures in suspension-cultured cells from a cryophyte (Chorispora bungeana)

Abstract: As the outermost boundary of the cell, the plasma membrane plays an important role in determining the stress resistance of organisms. To test this concept in a cryophyte, we analyzed alterations of several components in plasma membranes isolated from suspension-cultured cells of Chorispora bungeana Fisch. & C.A. Mey in response to treatment at 0 and -4 degrees C for 192 h. When compared with the controls growing at 25 degrees C, both the membrane permeability and fluidity showed recovery after the initial impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…To adapt to low temperature environment, many physiological and molecular changes occur during cold acclimation (Thomashow, 1999). Exposure to low temperature, linolenic acid and membrane lipid unsaturation increased, and the plasma membrane H + -ATPase activity increased and these changes are essential for the plants to withstand low temperature (Shi et al, 2008). In addition, calcium-dependent protein kinase confers cold tolerance via the regulation of calcium channel in plasma membrane (Xiong et al, 2002; Komatsu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To adapt to low temperature environment, many physiological and molecular changes occur during cold acclimation (Thomashow, 1999). Exposure to low temperature, linolenic acid and membrane lipid unsaturation increased, and the plasma membrane H + -ATPase activity increased and these changes are essential for the plants to withstand low temperature (Shi et al, 2008). In addition, calcium-dependent protein kinase confers cold tolerance via the regulation of calcium channel in plasma membrane (Xiong et al, 2002; Komatsu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the callus and suspension cells from C. bungeana were ready to endure freezing temperature (−4°C) without cold acclimation [3,6]. The aim of this study is to examine what kinds of mechanisms contribute to the specific cold tolerance of C. bungeana .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, PM H ? -ATPase activity increased during cold treatment exposure and finally displayed similar activity to the enzyme maintained at 25°C (Shi et al 2008). These findings suggest that this cryophyte adapts its plasma membrane in order to withstand low temperatures.…”
Section: Interaction With Sterols: the Planar Solutionmentioning
confidence: 59%
“…Changes in H ? -ATPase activity have also been reported (Jian et al 1982;Ishikawa and Yoshida, 1985;White et al 1990;Martz et al 2006;Zhang et al 2006;Shi et al 2008;Janicka-Russak et al 2012;Kim et al 2013;Oh et al 2014;Zhou et al 2014). The mechanisms behind these changes are not yet known in detail, but cold acclimation seems to be associated with modifications of the membrane lipid composition and their effects on the PM H ?…”
Section: Interaction With Glycerolipids: the Real World Of The Membramentioning
confidence: 71%
See 1 more Smart Citation